TINJAUAN TERHADAP PERKAWINAN DI BAWAH TANGAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Desy Fitriana Pawestri (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACT This study aims to find out how the legal status of children and wives in marriage is under the hands of based on Law Number 1 of 1974 concerning marriage and how the solution if there is a marriage under the hands to become lawful according to National law. The type of research used in this study uses the normative juridical method, namely by using the object of research studies in the form of the books in question as well as legislation that has a correlation with the discussion of issues related to research.When marriage is agreed upon, it must be agreed upon in harmony and marital conditions concerning the prospective bridegroom, prospective bride, bride guardian, two voters and qabul. Based on Law No. 1 of 1974 concerning Marriage in addition to fulfilling marital requirements must be recognized by the Marriage Registration Officer approved must be regulated in Article 2 paragraph (2) of Act Number 1 of 1974 concerning Marriage intended According to the applicable legislation, approved marriage is not registered with the Employer of Marriage Registration, the marriage is considered illegal according to national law and will affect the status of the wife and child. The status of the wife from under the marriage will cause several consequences, among others: the wife is not considered a legitimate wife, the wife does not have legal force in the event of a dispute and also the distribution of inheritance if the husband finds the world, the wife is neglected for rights and consequences, vulnerable to domestic violence, and the wife will find it difficult to socialize. As well as having an impact on children who determine because the status of children considering being a child is illegal and only has a relationship with family and permission. The solution that can be done is by applying for a marriage permit application to the Religious Court, besides that it can also do a remarriage that must be completed with a marriage registration by a supported official. For the government, it is expected to intensify the socialization of the importance of marriage registration so that all people really understand the marriage record, for the community there is a need for legal awareness to grow for each individual who allows to carry out under-the-hand marriage which has become a risk requirement.